The Item versus the Object in Memory: On the Implausibility of Overwriting As a Mechanism for Forgetting in Short-Term Memory - Beaman, C. Philip; Jones, Dylan M. (Frontiers in Psychology, 2016)
The nature of forgetting in short-term memory remains a disputed topic, with much debate focussed upon whether decay plays a fundamental role (Altmann & Schunn, 2012; Barrouillet, De Pape & Langerock, 2012; Berman, Jonides & Lewis, 2009; Neath & Brown, 2012; Oberauer & Lewandowsky, 2013; Ricker, Vergauwe & Cowan, 2014) but much less focus on other plausible mechanisms. One such mechanism of long-standing in auditory memory is overwriting (e.g., Crowder & Morton, 1969) in which some aspects of a representation are "overwritten" and rendered inaccessible by the subsequent presentation of a further item. Here, we review the evidence for different forms of overwriting (at the feature and item levels) and examine the plausibility of this mechanism both as a form of auditory memory and when viewed in the context of a larger hearing, speech and language understanding system.